2016
DOI: 10.1016/j.devcel.2015.12.027
|View full text |Cite
|
Sign up to set email alerts
|

Maternal DNA Methylation Regulates Early Trophoblast Development

Abstract: SummaryCritical roles for DNA methylation in embryonic development are well established, but less is known about its roles during trophoblast development, the extraembryonic lineage that gives rise to the placenta. We dissected the role of DNA methylation in trophoblast development by performing mRNA and DNA methylation profiling of Dnmt3a/3b mutants. We find that oocyte-derived methylation plays a major role in regulating trophoblast development but that imprinting of the key placental regulator Ascl2 is only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
79
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(84 citation statements)
references
References 63 publications
1
79
1
3
Order By: Relevance
“…23,24 In agreement with these results, we found that DNMT3A is necessary for the migration and invasion of trophoblast cells and is dysregulated in PE. In addition, the functions of other DNMTs in embryonic development have also been studied.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…23,24 In agreement with these results, we found that DNMT3A is necessary for the migration and invasion of trophoblast cells and is dysregulated in PE. In addition, the functions of other DNMTs in embryonic development have also been studied.…”
Section: Discussionsupporting
confidence: 79%
“…23 Furthermore, it has been proved that maternal deletion of Dnmt3a/b causes the defects of trophoblast development at embryonic day 9.5, which is represented by a deficient labyrinthine layer and a low-density trophoblast giant cell layer, possibly as a result of decreased cell adhesion and migration. 24 However, little is known about the role of DNMT3A in PE.…”
mentioning
confidence: 99%
“…Accordingly, SCML2 plays a role in modulating the cell-cycle machinery and impacts the cellular activity when it is ectopically expressed in transformed or cancer cells (28,29). In addition, there is evidence suggesting that SCML2 may be involved in human tumors, including malignant pediatric brain tumors, acute myeloid leukemia and human hepatocellular carcinoma (30)(31)(32)(33)(34)(35)(36). The above knowledge about SCML2, together with previous findings on SCML2 expression in islet-cell carcinoma (12)(13)(14), inspired the investigation of a more explicit linkage between SCML2 and GEP-NETs, a tumor with an increasing incidence worldwide, in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Keep in mind that the processes of growth and transcriptional efficiency, coupled to histone modifications required for the expression of housekeeping and maternal effect gene products (11), involve dynamic histone changes that precede imprinting methylations (12). Moreover, these stage-specific methylation marks of both imprinted and nonimprinted varieties control later developmental events bearing directly on implantation and trophectoderm development (13). Again, the paper by Morohaku et al (1) validates appropriate epigenetic modifications at each stage, then confirms the documented oocytes will give rise to healthy offspring.…”
Section: Significance and Future Applicationsmentioning
confidence: 99%